1503 Reduced life satisfaction in norwegian medical doctors compared to others: a 15-year longitudinal study on increased importance of work-related factors. (24th April 2018) - Mahmood, Javed Iqbal; Grotmol, Kjersti Støen; Tesli, Martin; Moum, Torbjørn; Andreassen, Ole; Tyssen, Reidar
Abstract : Introduction: There have been alarming reports about burnout and dissatisfaction in US doctors, but what about doctors in Scandinavian public health? We lack representative and longitudinal studies on adjusted work-related predictors of well-being in medical doctors. This study aims to compare Norwegian doctors' life satisfaction with a socio-economical matched population sample, and to analyse long-term work-related predictors of life satisfaction. Methods: Two nationwide cohorts of doctors (n=1052) were surveyed in their final year of medical school (1993/94 and 1999) (T1), and 4 (T2), 10 (T3), and 15 (T4) years later. The population sample was from the Nord-Trøndelag Health Survey. A one-item life satisfaction measure was used for the comparison. Work-related predictors of life satisfaction (3-items) from T2 to T4 were analysed and controlled for confounders by mixed models repeated measures. Results: Ninety per cent (947/1052) responded at least once, whereas 42% (450/1052) responded at all 4 periods. The population sample was n=595. Life satisfaction level was lower in doctors at T4 than in the comparison group (5.3 vs 5.7, p<0.001), and more doctors were dissatisfied with their life (5.6 vs 2.2%, p=0.006). Adjusted work-related predictors of higher life satisfaction were: work-home stress (β=−0.20, 95% CI=−0.25- −0.16, p<0.001), perceived job demands (β=−0.10, 95% CI=−0.15- −0.05, p<0.001), and colleague support (β=0.05, 95% CI: 0.04 to 0.07, p<0.001). Work-related predictors were more important in the youngest cohort (1999). Discussion: Dissatisfaction with life was almost three times more common among doctors, and work pressures seem to have increased over the last decade. The identified work-related factors seem to be especially important for doctors, and may partly explain the difference between doctors and others. We have controlled for relevant individual factors, such as personality, social support and negative life events, and also life style factors (such as problematic drinking and physical training).